2021
DOI: 10.1186/s12944-021-01497-7
|View full text |Cite
|
Sign up to set email alerts
|

High-density Lipoprotein Cholesterol Is Negatively Correlated with Bone Mineral Density and Has Potential Predictive Value for Bone Loss

Abstract: Background Many studies have shown that lipids play important roles in bone metabolism. However, the association between high-density lipoprotein cholesterol (HDL-C) and bone mineral density (BMD) is unclear. Therefore, this study aimed to investigate the linear or nonlinear relation between HDL-C levels and BMD and addressed whether the HDL-C levels had the potential values for predicting the risk of osteoporosis or osteopenia. Methods Two researc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 39 publications
3
29
1
Order By: Relevance
“…Recently, a group of studies has been demonstrated the roles of MetS in the pathological development of OP [ 19 , 20 ]. Analysis of data from the National Health and Nutrition Examination Survey (NHANES) database shows that the levels of high-density lipoprotein cholesterol are negatively associated with BMD, particularly in females [ 21 ]. The important roles of lipid metabolism in bones have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a group of studies has been demonstrated the roles of MetS in the pathological development of OP [ 19 , 20 ]. Analysis of data from the National Health and Nutrition Examination Survey (NHANES) database shows that the levels of high-density lipoprotein cholesterol are negatively associated with BMD, particularly in females [ 21 ]. The important roles of lipid metabolism in bones have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that HDL-c levels could be a useful parameter to determine the postmenopausal women whose BMD should be evaluated (D'AMELIO et al, 2008), and this could be further investigated in the ED population. Investigations with data from women between the ages of 20 and 60 years confirmed an inverse U-shaped association between levels of HDL-c and BMD, in which high levels mg/dL), comparable with the ranges found for the AN group in the present study, increased the risk of osteopenia and osteoporosis (TANG et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…11 Moreover, the subset analyses of the NHANES database showed that high-density lipoprotein cholesterol (HDL-C) is negatively correlated with BMD, suggesting that HDL-C may have potential predictive for bone loss. 9 In addition, the causal relationship blood lipid and BMD is still largely unknown. These inconsistent findings may come from the inclusion for population with different age, gender, physiological state and accompanying diseases, laboratory measurements and questionnaires, and different correction method of confounding factors such as body mass index (BMI) and lifestyles.…”
Section: Introductionmentioning
confidence: 99%